Knowledge, barriers and facilitators regarding COVID-19 vaccine and vaccination programme among the general population: A cross-sectional survey from one thousand two hundred and forty-nine participants. Issue 3 (May 2021) - Kumari, Archana; Ranjan, Piyush; Chopra, Sakshi; Kaur, Divjyot; Kaur, Tanveer; Upadhyay, Ashish Datt; Isaac, Joshua Abraham; Kasiraj, Rhytha; Prakash, Bindu; Kumar, Parmeshwar; Dwivedi, Sada Nand; Vikram, Naval K.
Abstract: Background and aims: The success of the COVID-19 vaccination program is dependent on people's knowledge and attitude regarding the vaccination program. Higher vaccine acceptance can be ensured by strengthening the facilitators and limiting the barriers being observed among the general population. Material and methods: Indexed study is a cross-sectional web-based survey using a pre-validated questionnaire to assess knowledge, barriers and facilitators of COVID-19 vaccine and vaccination programme administered on adults across India using a Google online survey platform. Results: A total of 1294 responses (age: 38.02 ± 13.34 years) were collected. Most of the participants had limited knowledge regarding the eligibility of vaccines in vulnerable population groups such as people with allergies (57.89%) and immune-compromised patients (62.98%), pregnant and lactating women (41.89%) and patients with chronic illness (34.78%). Older participants (>45 years) were more willing to take the COVID-19 vaccine (p < 0.001) as they believed the vaccine is not harmful and considered it as societal responsibility. Younger participants (<45 years) and those residing in urban settings raised concerns on the availability of the vaccine and authenticity of the vaccine (p < 0.001). Conclusion: There is a scope for improvement in people's knowledge regarding COVID-19 vaccine and the vaccination programme by addressing the barriers and facilitators which can improve the participants' turnover at vaccination centres. Highlights: Participants had limited knowledge regarding the eligible candidates for the vaccine. Older population (>45 years) were more willing to get the vaccine. People belonging to higher socio-economic status and residing in urban areas were more willing to get vaccinated.